Research on energy policies of Jiangxi province under the dual-carbon constraints - Xinfa, Tang; Xue, Luo (Frontiers in Environmental Science, 2022)
As a region with a good ecological foundation and a strong carrying capacity of resources and environment, Jiangxi Province of China was included in the first batch of unified and standardized national ecological civilization experimental zones as early as 2016. How to realize carbon neutrality and carbon peak was the long-term key task of Jiangxi Province and the energy policy was the main effective means for Jiangxi Province to achieve high-quality economic and social development during the 14th Five-Year Plan period. Therefore, based on Bayesian Nash equilibrium theory, a carbon game analysis between enterprises and government under double carbon constraints was established. Besides, by relying on the current situation of energy consumption and carbon emission in Jiangxi Province of China, the goal path of achieving carbon neutrality and carbon peak in Jiangxi Province was tested. According to the research, with lack of natural resources and energetic development of low-carbon economy, enterprises and governments should make transpositional consideration to balance interests and realize common development amid cooperation, thus achieving the harmonious development of society. It is necessary to deepen the understanding of peak carbon dioxide emissions and carbon neutrality, analyze how Jiangxi Province solves the challenges and realization pathways under the goal of peak carbon dioxide emissions and carbon neutrality and discuss policy demands, which are of vital significance for the realization of low-carbon transformation and upgrading of China’s economy and society.